Denmark Vesey's Revolt : The Slave Plot That Lit a Fuse to Fort Sumter - Lofton, John (Book collections on Project MUSE., 2013)
In 1822, Denmark Vesey was found guilty of plotting an insurrection--what would have been the biggest slave uprising in U.S. history. A free man of color, he was hanged along with 34 other African Americans in Charleston, South Carolina, in what historians agree was probably the largest civil execution in U.S. history. At the time of Vesey's conviction, Charleston was America's chief slave port and one of its most racially tense cities. Whites were outnumbered by slaves three to one, and they were haunted by memories of the 1791 slave rebellion in Haiti. This book draws upon primary sources to examine the trial and provide, as Peter Hoffer says in his introduction, "one of the most ... measured" accounts of the subject